Britain returns Chagos Islands to Mauritius: a victory for small states? - Wang, Yuchen (2024)
Last month, the United Kingdom decided to return the Chagos Islands to Mauritius, marking a critical juncture in international relations, particularly for the small states attempting to assert their sovereignty against former colonial powers. The resolution of this decades-long dispute raises key questions about the capacity of small states to utilise international law, multilateral diplomacy, and support from international organisations to challenge more powerful states. It also highlights the changing dynamics of global governance and the possibilities for post-colonial justice.